PERANCANGAN SISTEM KLAIM REIMBURSEMENT BERBASIS WEB UNTUK MENINGKATKAN SEMANGAT KERJA KARYAWAN PADA PERUSAHAAN - Pakpahan, Roida; Fitriyani, Yuni; Kholik, Abdul (Journal of Information System, Informatics and Computing, 2025)
Reimbursement is a replacement of funds made by the company to employees who have incurred personal costs in advance for the benefit of the company. Generally, companies apply a reimbursement system to employees in carrying out their work where employees must pay for their own operational costs and other needs and then these costs will be claimed to the company's finance or human resource development department. In practice, manual reimbursement of operational costs using the reimbursement system takes a long time and this will affect employee morale because it will directly affect the employee's financial condition. With the advancement of technology, the employee reimbursement claim system can be carried out using web-based digital technology where employees can submit claims for costs that have been used online. The purpose of this study is to analyze and provide solutions to the problems of the employee reimbursement claim system which is still done manually. The research method uses the waterfall method. The results of the study show that the web-based employee reimbursement claim system increases the efficiency of the claim process time in the company because employees can submit operational costs that have been incurred in real time. On the other hand, the online reimbursement system can increase employee morale because the replacement of funds that have been used can be processed faster.